2010
DOI: 10.1002/pssc.200982634
|View full text |Cite
|
Sign up to set email alerts
|

Deep traps analysis in AlGaN/GaN heterostructure transistors

Abstract: AlGaN/GaN high electron mobility transistors are investigated by DLTS measurements. 6 different are extracted with the following activation energies: 0.12 eV, 0.15 eV, 0.21 eV, 0.42 eV, 0.49 eV and 0.94 eV. Based on comparison with literature results and measurements as a function of the pulse reverse bias, the trap localisation in the structure is discussed. Additional measurements as a function of the filling pulse duration reveal the presence of decorated extended defects in the samples. (© 2010 WILEY‐VCH V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In Ref. [271] DLTS measurements were performed on Schottky diodes of test FET structures prepared on MOCVD-grown AlGaN/GaN. The authors observed a measurable hysteresis of C-V characteristics at low temperatures, but no strong shift of the threshold voltage of the type described by Figs.…”
Section: Algan/gan Heterojunctions: the Origin Of Two-dimensional Gasmentioning
confidence: 97%
“…In Ref. [271] DLTS measurements were performed on Schottky diodes of test FET structures prepared on MOCVD-grown AlGaN/GaN. The authors observed a measurable hysteresis of C-V characteristics at low temperatures, but no strong shift of the threshold voltage of the type described by Figs.…”
Section: Algan/gan Heterojunctions: the Origin Of Two-dimensional Gasmentioning
confidence: 97%
“…We assumed two types of deep traps at the interfaceacceptor type and donor type traps [18][19][20]. Acceptor type traps are neutral when they are empty and negative when they are occupied by electron.…”
Section: Theorymentioning
confidence: 99%
“…Since this charge has large time constants the transistor properties are time dependent which also influences their stability. According to experimental results these traps are prevalently concentrated at the AlGaN and GaN layers interface [1][2][3], but also in AlGaN or in GaN layer [4]. Interface traps are also a reason for capacitance hysteresis in AlGaN/GaN heterostructures [5].…”
Section: Introductionmentioning
confidence: 96%
“…The presence of extended defects due to dislocations mostly located at the AlGaN/GaN hetero-interface was also confirmed by Fourier Transform (FT-DLTS) technique. 21 Therefore, good quality MOCVD AlGaN/GaN HEMT heterostructures were grown using thick buffer layers with reduced D D-edge as observed from the XRC results as well as smoother interface with low D it-min value as evident from improved carrier transport properties.…”
mentioning
confidence: 99%